A5_12 World’s Greatest Pitch - Keany, Connor; Graham, Thomas; Kaiser, Felix; Newland, Rhys; Pankhania, Kishen (Physics Special Topics, 2022)
The goal of this paper was to investigate the possibility of an ordinary human to recreating a scene from the first episode of the series Invincible in which two characters throw a baseball around the Earth. It is determined that this scene would be impossible to recreate on Earth, however it could be done on a planet with a radius of 67.03 x 103m, roughly 1/100th that of Earth.